Writing the Ethnic Origins of the Rasulids in Late Medieval South Arabia. (October 2018) - Mahoney, Daniel
The Rasulids arrived in South Arabia towards the end of the sixth/twelfth century as Turkoman officers in the Ayyubid military. Thereafter they established a dynasty that lasted until the mid-ninth/fifteenth century. At the height of their power at the end of the seventh/thirteenth century, an effort to further buoy their political legitimacy was undertaken by resituating their ethnic origins to South Arabia. This first appeared within a genealogy that simultaneously showed their emergence from the complex web of descent of the local tribes, as well as juxtaposed them with the rulers of the Islamic Caliphate and elevated them above other contemporary political groups in South Arabia. However, after the Rasulid military was increasingly challenged over the course of the eighth/fourteenth century and the dynasty's influence in the region and the wider Islamic world continued to dissipate, the assertion of their local origins was greatly fleshed out into a narrative at the beginning of a dynastic chronicle of the early ninth/fifteenth century. This prologue explains more explicitly how they first emigrated from South Arabia in the pre-Islamic period only to then return in the late medieval period as its rightful rulers. Overall, the construction of this origin story points to the Rasulids' attempt to take on a new strategy of identification through the appropriation of South Arabian cultural memory in order to strengthen their political status.